Placental tissue metabolome analysis by GC-MS: Oven-drying is a viable sample preparation method. Issue 6 (3rd July 2018) - Troisi, Jacopo; Symes, Steven; Adair, David; Colucci, Angelo; Prisco, Sonia Elisa; Aquino, Carmen Imma; Vivone, Immacolata; Guida, Maurizio; Richards, Sean
Abstract: Analysis of the human placenta metabolome has great potential to advance the understanding of complicated pregnancies and deleterious fetal outcomes in remote populations, but samples preparation can present unique challenges. Herein, we introduce oven-drying as a simple and widely available method of sample preparation that will facilitate investigations of the placental metabolome from remote and under-studied populations. Placentae from complicated and uncomplicated pregnancies were prepared in three ways (oven-dried at 60 °C, fresh, lyophilized) for metabolome analysis via gas chromatography-mass spectrometry (GC-MS). Multiple computer models (e.g. PLS-DA, ANN) were employed to classify and determine if there was a difference in placentae metabolome and a group of metabolites with high variable importance in projection scores across the three preparations and by complicated vs. control groups. The analyses used herein were shown to be thorough and sensitive. Indeed, significant differences were detected in metabolomes of complicated vs. uncomplicated pregnancies; however, there were no statistical differences in the metabolome of placentae prepared by oven-drying vs. lyophilization vs. fresh placentae. Oven-drying is a viable sample preparation method for placentae intended for use in metabolite analysis via GC-MS. These results open many possibilities for researching metabolome patterns associated with fetal outcomes in remote and resource-poor communities worldwide.